A further physiological role for naturally occurring trypsin inhibitors: the evidence for a trophic stimulant of the pancreatic acinar cell. Issue 12 (December 1969) - Melmed, R. N.; Bouchier, I. A. D.
Abstract : The oral ingestion of naturally occurring purified trypsin inhibitors from soybean, ovomucoid, and bovine pancreas has been demonstrated to be a potent stimulus to pancreatic digestive enzyme synthesis. This effect may be so marked as to lead to impairment of growth in the rat and chicken through the faecal loss of essential amino acids. This is thought to be due to the markedly potentiated secretion of pancreatic digestive enzyme protein overwhelming the normal digestive capacity of the gastrointestinal tract and resulting in a pancreatogenous protein-losing enteropathy. Experimental evidence is presented to suggest that this response to the trypsin inhibitors requires the mediation of the gastrointestinal tract and is independent of vagal innervation to the pancreas. The most satisfactory hypothesis would favour the release of a trophic stimulus from the intestinal mucosa (possibly pancreozymin-cholecystokinin) to the acinar cell of the pancreas in response to the presence of the trypsin inhibitor in the bowel lumen. It is suggested that a primary function of the endogenously secreted pancreatic trypsin inhibitor may be to potentiate enzyme synthesis by the acinar cell, providing an important stimulus for the repletion of the digestive enzymes. Some of the potential physiological and clinical implications of such a mechanism are discussed.